Rhizobacterial Inoculation to Enhance Growth and Productivity of Fenugreek - Irum, Ayesha; Khan Pasha, Muhammad Farhan; Aziz, Huma; Muhammad Akram; Waseem Ur Rehman; Abdul Momin; Naheed, Rafia; Mubeen, Aniqa; Sami Ullah (Indus Journal of Bioscience Research, 2024)
The use of rhizobacterial inoculants represents a promising strategy to improve crop productivity and sustainability. This study investigates the impact of four different rhizobacterial strains on the growth and productivity of fenugreek (Trigonella foenum-graecum). Conducted under field conditions, the experiment followed a randomized complete block design with four replications. The treatments included inoculation with individual strains as well as a control with no inoculation. Key growth parameters, such as germination rate, plant height, biomass, nodulation, and seed yield, were systematically recorded. The results demonstrated significant enhancements in fenugreek growth and yield in response to rhizobacterial inoculation compared to the control. Strain F1 showed the highest increase in germination rate and plant height, while Strain F2 resulted in the maximum biomass accumulation. Strain F3 significantly improved nodulation and overall root development, contributing to better nutrient uptake. Strain F4 produced the highest seed yield, indicating its potential in enhancing fenugreek productivity. All inoculated treatments exhibited improved soil health indicators, such as increased microbial activity and nutrient availability, compared to the control. The combined analysis revealed that the use of these rhizobacterial strains not only promoted plant growth but also contributed to sustainable agricultural practices by enhancing soil fertility. This study underscores the potential of specific rhizobacterial strains in boosting fenugreek production and provides a foundation for the development of effective microbial inoculants. Further research on the synergistic effects of these strains and their application methods could optimize their benefits, offering a viable solution for enhancing crop yield and soil health in legume cultivation.